"استخدام مرشّح كالمان في رصد الحالة الحركية للمنشآت الهندسية" - فحصة, إياد إسماعيل; أحمد, محسن مزيد; سخية, تمام فريد (Latakia University Journal -Engineering Sciences Series, 2016)
يجب أن تحقّق شبكات المراقبة الجيوديزية شروط الدقّة والديمومة والقوّة والحساسية والكلفة. وعلى هذا الأساس يتم تصميم شبكات المراقبة الجيوديزية. تتحكم الأجهزة المساحية الأرضية الحديثة بالعمليات الحركية وبتردد عالي من القياسات، وبالتالي يمكن تحديد حالة النظام، ودقّته في الزمن الحقيقي وفقاً لنموذج التشوه المناسب. في هذا البحث، تمّ تقييم كفاءة مرشح كالمان الخطي في تحسين أداء شبكات المراقبة الجيوديزية خاصّةً المستخدمة حالياً في مراقبة المنشآت الاستراتيجية في القطر، وتحقيق أعلى مستوى من الأمان في مراقبتها وتطوير مستوى الموثوقية والمتانة فيها، وتطبيق ذلك على الحالة الحركية المرصودة لمنشأة سد 16 تشرين في محافظة اللاذقية. ومن ثم التحقّق من كفاءة التقييم، بتطبيق معايير الموثوقية، ومدى ملاءمة تطبيق مرشح كالمان في تحليل التشوه. وقدّم البحث مجموعة من الاستنتاجات والتوصيات. Geodetic monitoring networks should check the requirements of precision, stability, durability, strength, sensitivity and cost. Depending on this basis design the geodetic monitoring networks. Terrestrial surveying instruments adjust kinematic processes by high frequency measurements; therefore can select system state and its precision in real time depending on appropriate deformation model. In this research, liner kalman filter will be evaluated to improve the performance of geodetic monitoring networks, especially the currently used in monitoring of strategic infrastructure in the country, and achieve the highest level of security in the monitoring and development level of reliability and durability where, and apply it to the observed kinematic situation in 16 tishreen dam in lattakia city. Then check the efficiency of the evaluation by applied standards reliability, and the appropriateness of the application of kalman filter in deformation analysis. Finally, this research offers a set of conclusions and recommendations.